Communication ethics in business: Examining the role of ethical communication in building trust and sustainability - Kalogiannidis, Stavros; Spinthiropoulos, Konstantinos; Chatzitheodoridis, Fotios; Kalfas, Dimitrios; Kantzios, Nikolaos (International Journal of Innovative Research and Scientific Studies, 2025)
Stakeholder confidence in a business is largely determined by how transparent the firm’s financial and non-financial information is. The purpose of this study was to examine the role of ethical communication in building trust and sustainability. A cross-sectional survey research design and a quantitative research methodology were used in the study. Data were collected from 360 different owners of businesses in Greece using a questionnaire. The study’s findings demonstrate the beneficial impact ethical business communication may have on a company’s capacity to survive unpredictable times. Additionally, the findings demonstrate that company viability in uncertain times is positively impacted by external and horizontal corporate communication. Research findings point to the need for a greater understanding of how to evaluate the openness of business information. Opportunities for business information transparency valuation have been revealed. These might be utilized to develop business information transparency evaluation methodologies or to have a different firm evaluate its own business information disclosure. People must successfully communicate both internally and externally using the proper forms of communication in order to plan and, as a result, develop sustainability as well as sustainable plans. Hence, when using ethical communication to improve company continuity during uncertain times, managers in respectable organizations should communicate with the recipient in a clear, direct, and accurate way. The findings have significant implications for the area of business management, most especially with regard to the value of business communication in ensuring the viability of companies in uncertain or crisis-ridden times.